Impacts of Newly Government-Inducted Teachers’ Performance on Learners’ Outcomes - Sara Fayyaz; Ajab Ali Lashari; Husan Bano Channar; Mansoor Ali Chang; Noor Bano; Saeeda Anjum Buriro (Al-Qanṭara, 2023)
This study aims to analyse how newly inducted teachers’ performance impacts learners’ outcomes in 6th to 10th-grade students’ public schools in Sindh. The study is quantitative and follows a survey research design. The data has been collected by personal visits by selecting a random sampling technique. The sample size of this study is 100 students. The translated version of the questionnaire has been used for the data collection, and SPSS has been used to quantify the data. The findings show that newly induced teachers’ performance positively impacts learners’ outcomes. The teachers use innovative teaching methods and strategies to cater to learners' needs, including academic achievement, exam scores, competencies development and positive change in learners’ behaviours. This study will be helpful for the policymakers, government bodies and school management for such initiatives to improve quality education and ensure good governance in education and literacy departments for desired outcomes to meet sustainable development goals.